Mass measurements of 56−57 Cr and the question of shell reincarnation at N=32 - Guénaut, Celine; Herfurth, Frank; Kluge, Heinz-Jürgen (Journal of physics. G, Nuclear and particle physics, 2005)
Binding energies determined with high accuracy provide smooth derivatives of the mass surface for analysis of shell and pairing effects. Measurements with the Penning trap mass spectrometer ISOLTRAP at CERN-ISOLDE were made for 56−57 Cr for which an accuracy of 4 × 10 −8 was achieved. Analysis of the mass surface for the supposed new N = 32 shell closure rather indicates a sub-shell closure, but of a different nature than known cases such as 94 Sr.